On the design and role of passive stabilisation within the ST40 spherical tokamak. (30th April 2018) - Buxton, P F; Asunta, O; Gryaznevich, M P; Lockley, D; McNamara, S; Medvedev, S; Ruiz de Villa Valdés, E; Whitfield, G; Wood, J M
Abstract: The position of passive stabilisation has been optimised for the low aspect ratio tokamak ST40. We find that passive stabilisation is most effective when conductors are placed near the plasma's x-point, and the combined effect of having both inboard and outboard passive stabilisation significantly reduces the vertical instability growth rate. The growth rate can be further decreased by cooling the passive conductors down to 80 K. Two concepts for passive stabilisation are considered, passive plates and passive coils, and the relative advantages and disadvantages of each are discussed. Both concepts involve connecting the upper and lower conductors in an 'anti-symmetric' manner, which prevents large currents from being induced.